1999
DOI: 10.1116/1.590780
|View full text |Cite
|
Sign up to set email alerts
|

Strain in AlGaN layer studied by Rutherford backscattering/channeling and x-ray diffraction

Abstract: An AlGaN layer with good crystalline quality (χmin=2.1%) was grown by metalorganic vapor phase epitaxy on a sapphire (0001) substrate using a GaN intermediate layer. The Al composition, which cannot be unambiguously determined by x-ray diffraction (XRD) or by photoluminescence, was determined by Rutherford backscattering (RBS). The perpendicular and parallel elastic strain of the Al0.28Ga0.72N layer, e⊥=−0.16% and e∥=+0.39%, respectively, were derived using XRD and RBS/channeling. The small ratio |e⊥/e∥|=0.41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In the unirradiated sample, the layers are partially relaxed and the AlGaN layer is still under a tensile strain of ε t = −0.55%. The χ min of the AlGaN layer is 12% and the GaN layer is 18% (23)(24)(25). This shows that the samples have a high defect density.…”
Section: Rbs/channelingmentioning
confidence: 90%
“…In the unirradiated sample, the layers are partially relaxed and the AlGaN layer is still under a tensile strain of ε t = −0.55%. The χ min of the AlGaN layer is 12% and the GaN layer is 18% (23)(24)(25). This shows that the samples have a high defect density.…”
Section: Rbs/channelingmentioning
confidence: 90%
“…Nowadays, silicides with a high degree of perfection can be fabricated on Si(111) in different ways: co-deposition, 12 sequential deposition, 8 -10 thin template layer, 8,9 solid phase epitaxy, 11 molecular beam epitaxy, 13 reactive deposition epitaxy, 14 ion implantation, 15 and ion beam epitaxy. 16 For thick layers, reactive deposition epitaxy or template layers provide the best surfaces because they produce a lower density of pinholes, whereas for low coverages, all methods give well-reconstructed surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…This method provides information about the Al content indirectly, since it is deduced from the relative shift of the Al x Ga 1 − x N reflection with respect to the GaN one. However, as it is well known, the shift in the peak can also be influenced by the presence of strain within the layer, making the analysis ambiguous [9]. Another disadvantage of the XRD analysis is that an Al profile analysis is not straightforward and may require tedious techniques, such as changing the incidence angle to explore different layer depths.…”
Section: Introductionmentioning
confidence: 98%
“…The suitability of these techniques to study GaNbased materials has been already reported [11]. Among IBA methods, Rutherford backscattering spectrometry (RBS) has been used to contrast with XRD analysis in AlGaN layers [9] and superlattices [12]. The advantage of RBS is that it can provide additional structural information by performing RBS in channelling mode (RBS/C) [13,14].…”
Section: Introductionmentioning
confidence: 99%